A rapid method for estimation of Pu-isotopes in urine samples using high volume centrifuge. (July 2017) - Kumar, Ranjeet; Rao, D.D.; Dubla, Rupali; Yadav, J.R.
Abstract: The conventional radio-analytical technique used for estimation of Pu-isotopes in urine samples involves anion exchange/TEVA column separation followed by alpha spectrometry. This sequence of analysis consumes nearly 3–4 days for completion. Many a times excreta analysis results are required urgently, particularly under repeat and incidental/emergency situations. Therefore, there is need to reduce the analysis time for the estimation of Pu-isotopes in bioassay samples. This paper gives the details of standardization of a rapid method for estimation of Pu-isotopes in urine samples using multi-purpose centrifuge, TEVA resin followed by alpha spectrometry. The rapid method involves oxidation of urine samples, co-precipitation of plutonium along with calcium phosphate followed by sample preparation using high volume centrifuge and separation of Pu using TEVA resin. Pu-fraction was electrodeposited and activity estimated using 236 Pu tracer recovery by alpha spectrometry. Ten routine urine samples of radiation workers were analyzed and consistent radiochemical tracer recovery was obtained in the range 47–88% with a mean and standard deviation of 64.4% and 11.3% respectively. With this newly standardized technique, the whole analytical procedure is completed within 9 h (one working day hour).